7(2x-1)=-4(6-2x)

Simple and best practice solution for 7(2x-1)=-4(6-2x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(2x-1)=-4(6-2x) equation:


Simplifying
7(2x + -1) = -4(6 + -2x)

Reorder the terms:
7(-1 + 2x) = -4(6 + -2x)
(-1 * 7 + 2x * 7) = -4(6 + -2x)
(-7 + 14x) = -4(6 + -2x)
-7 + 14x = (6 * -4 + -2x * -4)
-7 + 14x = (-24 + 8x)

Solving
-7 + 14x = -24 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
-7 + 14x + -8x = -24 + 8x + -8x

Combine like terms: 14x + -8x = 6x
-7 + 6x = -24 + 8x + -8x

Combine like terms: 8x + -8x = 0
-7 + 6x = -24 + 0
-7 + 6x = -24

Add '7' to each side of the equation.
-7 + 7 + 6x = -24 + 7

Combine like terms: -7 + 7 = 0
0 + 6x = -24 + 7
6x = -24 + 7

Combine like terms: -24 + 7 = -17
6x = -17

Divide each side by '6'.
x = -2.833333333

Simplifying
x = -2.833333333

See similar equations:

| X(25+10)=45 | | 90+0.3m=70+.5m | | 2x=3(1-x)-(x+1) | | -6=5+e | | -2(y-3)=-3(6-2y) | | 2(z+1)=3(z-4) | | 5m-2m+16=10 | | -7x+49=7 | | 13=3y+9 | | 3m-m=3 | | 11-4p=26-9p | | 7x-12=4x+30 | | 2(8n-10)=9n+8 | | 5.4a-12.7=1.3-1.6a | | -5=13-3M | | 2x^2-20x-78=0 | | -7+3x=-73 | | 10*x-2*5=16 | | -3(+5)=3(x-1) | | -3+4x=-35 | | 5x^6=-320 | | 5m+3=9-4m | | 5x+6=2-3x | | 2(2y+7)-9y=-2(3-5y)+5 | | 10+6x=46 | | 2x+7=14+5x | | 16=3x+3 | | 100/5/2*5=16 | | 8x+9=2(7x-6) | | 13*4-22/11+5*x=75 | | 40+3x=-20 | | (3+w)w+w+(3+w)=24 |

Equations solver categories